Pemberdayaan Guru SMPN 1 Singorojo Kabupaten Kendal melalui Pelatihan Wordwall untuk Mengoptimalkan Pembelajaran Interaktif - Eny Hartadiyati Wasikin Haryanti (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
Optimizing interactive learning through the integration of digital technology, particularly the use of the Wordwall platform, is crucial in 21st-century education. However, many teachers at SMPN 1 Singorojo, Kendal Regency, have not yet maximized their potential. This Community Service Program aims to empower teachers through training in the use of Wordwall to optimize interactive learning. A total of 28 teachers from various subjects participated in an 8-hour training session consisting of theoretical and practical components, followed by an evaluation. The theoretical session on interactive learning and the Wordwall platform showed that at least 80% of participants reached the understanding to very understanding category. In the practical session, 80% of teachers successfully created at least one interactive media using Wordwall features such as Group Sort, Quiz, and Spin the Wheel. These results indicate that this training effectively impacted teacher independence in optimizing interactive learning using the Wordwall platform at SMPN 1 Singorojo, Kendal Regency.